Analisis Kebijakan Program Beasiswa Sepuluh Sarjana Per Desa di Kabupaten Bojonegoro - Sari, Elsa Andhita; Huda, Muhammad Miftahul; Rupiarsieh, Rupiarsieh (Universitas 17 Agustus 1945 Surabaya, 2023)
Bojonegoro Regency is an oil and gas producing area with a total APBD of Bojonegoro Regency reaching 7.4 trillion, most of the budget comes from oil and natural gas products. However, the Human Development Index (HDI) achievement in Bojonegoro Regency is in the fifth lowest position in East Java due to the low quality of education in Bojonegoro Regency. The policy taken by the government to overcome this problem is the Ten Scholars Scholarship Program Per Village, which is expected to increase the interest of the people of Bojonegoro in continuing their education at university. This research aims to understand the cause and effect of the policy process for the Ten Scholars Per Village scholarship program in Bojonegoro Regency in overcoming the low quality of human resources in Bojonegoro Regency. This research uses a descriptive qualitative method with data sources obtained from the results of field studies through interviews, observation, and documentation techniques. The results of this research are that the Ten Scholars Per Village scholarship program in Bojonegoro Regency has been implemented by Perbup Number 17 of 2023. However, there are several obstacles to its implementation. The existence of this program policy can have a positive impact on increasing the HDI achievement of Bojonegoro Regency from medium scale to high scale.